2018
DOI: 10.26833/ijeg.377080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the utility of the unmanned aerial vehicle (UAV) in volume calculation by using photogrammetric techniques

Abstract: Together with developments in software technology, various interpolation methods allow terrain surfaces to be better identified. The accuracy rate in volume calculations is directly proportional with representation in the best form. The non-metric cameras, which are assembled to unmanned aerial vehicles (UAVs), provide convenience in the photogrammetric measurements. Sensitive images are obtained with less cost by the use of unmanned aerial vehicles. The purpose of this study was to take photos from the air wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 7 publications
(6 reference statements)
0
9
0
4
Order By: Relevance
“…Accurate DEM generated using UAV images provides cost effective data and proved that it is time-saving for earthwork in engineering works especially in road designing on lands with low vegetation or bare ground (Akgul et al, 2017). (Ulvi̇, 2018) accentuated that, there was a fourfold increase in the time required for volume calculation using classical methods than using UAV techniques as well as there was 99.33% agreement between volumes calculated by UAV and GPS methods. (Arango & Morales, 2015), demonstrated that volume estimation by means of UAV-based DEM is more accurate than traditional method with total station as well as it is faster than total station by six times in term of data acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accurate DEM generated using UAV images provides cost effective data and proved that it is time-saving for earthwork in engineering works especially in road designing on lands with low vegetation or bare ground (Akgul et al, 2017). (Ulvi̇, 2018) accentuated that, there was a fourfold increase in the time required for volume calculation using classical methods than using UAV techniques as well as there was 99.33% agreement between volumes calculated by UAV and GPS methods. (Arango & Morales, 2015), demonstrated that volume estimation by means of UAV-based DEM is more accurate than traditional method with total station as well as it is faster than total station by six times in term of data acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…The result of their study showed that the error in volume for stockpile and trench in comparison with GPS survey were found about ±206.94 ft3 (7%) and ±3311.4563 ft3 (0.9%) respectively. (Ulvi̇, 2018), analyzed the utility of unmanned aerial vehicle in volume calculation. The volume calculation was made by both photogrammetric technique and conventional survey methods.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade UAV map production systems have become an important technology for different disciplines (Akgül et al 2016;Öztürk et al 2017;Ulvi 2018;Ulvi and Toprak 2016;Ulvi et al 2020). The main reason for the spread of this system is the availability of flight platforms and technology for civilian users, as well as reductions in costs.…”
Section: Introductionmentioning
confidence: 99%